Studi Literatur Pemikiran Ki Hajar Dewantara Terkait Filosofi Pendidikan dalam Kurikulum Merdeka di Indonesia - Indah Aditya Putri; Liesna Andriany (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
Ki Hajar Dewantara’s thinking about educatonal include lifelong learning that adapts to changing circumstances, take a lot of variety sources and consistent with indonesian pancasila dan cultural norms. This concept can been practicing following by merdeka curriculum. Th purpose of this study is to certain Ki Hajar Dewantara’s thinking of values and their applicability in education philosophy with merdeka curriculum. The methods in this study is qualitative descriptive in study literarature on some journal that related. The results of this study show that Ki Hajar Dewantara’s thinking tell about how important education when we can value the student’s freedom, independence dan uniqueness.